The Effect of Tea Party Learning Model on English Speaking Skills at Fourth Grade Students of MI Darul Ulum - Sintawati, Fairus; Soraya, Kety; Rosnaningsih, Asih; Wulan, Putri Cahya (JEDLISH : Journal Of Education and English Language Teaching, 2022)
This study aims to determine the effect of the Tea Party learning model on English speaking skills. This study uses a quantitative approach, and the type of research used is experimental research. This research instrument used speaking skill test (pretest and posttest). The population of this study was the fourth-grade students of MI Darul Ulum, totalling 54 students, while the sampling technique was carried out with a saturated sample, that is, all of the population were used as samples of research. Based on the results of research and data analysis, students who were taught by applying the Tea Party learning model had an effect on the speaking skills. This can be proven by the significant level of = 0.05. From this value, it is obtained that t-count > t-table is 3,492 > 2,007, so Ho is rejected and H1 is accepted, so it can be concluded that through the application of the Tea Party learning model, students can improve speaking skills at the fourth-grade students of MI Darul Ulum.